THE INFLUENCE OF EMOTIONAL DISSONANCE, EMOTIONAL INTELLIGENCE AND ORGANIZATIONAL COMMITMENT ON JOB SATISFACTION OF EMPLOYEES OF BANK BUMN IN INDONESIA - Krishnabudi, Nyoman Gede; Utami, Wiji; Sudarsih, Sudarsih (Jurnal Istiqro, 2020)
This study aims to determine emotional dissonance, emotional intelligence as well as organizational commitment and their influences on job satisfaction of employees of Bank BUMN (state-owned banks) in Indonesia. The approach used in this research is a quantitative approach. The research population is 283 front office employees from 7 state-owned banks in Indonesia consisting of tellers, customer services staff, and marketing staff. All the 283 populations studied entirely. The methods of data analysis used multiple linear regression analysis. The results of test and analysis show that emotional dissonance has a negative and significant effect on job satisfaction of employees of Bank BUMN in Indonesia, emotional intelligence has a significant effect on employee job satisfaction and commitment have a positive and significant impact on job satisfaction of employees of Bank BUMN in Indonesia.